Main Stages of the Formation of an Economic Cluster - Mindlin, Yurii B.; Zhukov, Boris M.; Prokhorova, Victoria V.; Shutilov, Fedor V.; Belova, Elena O. (International Journal of Economics and Financial Issues, 2016)
The questions of the formation of cluster, their management and development in economy of Russia became in recent years a topic of numerous discussions, research studies by domestic economists. Cluster strategies of development are widespread in public authorities. Moreover, there are official documents considering the contents and directions of the main new formed economic clusters. Foreign and domestic scientists have more than once proved that development of countries, where a cluster approach is used, characterizes increased production efficiency, competitiveness growth, increasing population welfare. This issue on the formation of an economic cluster is urgent both for the state and other entities. Also the process of realization and introduction of this economic event is quite important. This paper is devoted to the main stages of the formation and application of an economic cluster. Keywords: stage, cluster, economic process, innovation, system JEL Classifications: A19, A39, O10